Baclofen into the lateral parabrachial nucleus induces hypertonic sodium chloride intake during cell dehydration - Kimura, Everton H. [UNESP]; De Oliveira, Lisandra B.; Menani, José Vanderlei [UNESP]; Callera, João Carlos [UNESP] (Springer Nature, 2013)
Background: Activation of GABAB receptors with baclofen into the lateral parabrachial nucleus (LPBN) induces ingestion of water and 0.3 M NaCl in fluid replete rats. However, up to now, no study has investigated the effects of baclofen injected alone or combined with GABAB receptor antagonist into the LPBN on water and 0.3 M NaCl intake in rats with increased plasma osmolarity (rats treated with an intragastric load of 2 M NaCl). Male Wistar rats with stainless steel cannulas implanted bilaterally into the LPBN were used.Results: In fluid replete rats, baclofen (0.5 nmol/0.2 μl), bilaterally injected into the LPBN, induced ingestion of 0.3 M NaCl (14.3 ± 4.1 vs. saline: 0.2 ± 0.2 ml/210 min) and water (7.1 ± 2.9 vs. saline: 0.6 ± 0.5 ml/210 min). In cell-dehydrated rats, bilateral injections of baclofen (0.5 and 1.0 nmol/0.2 μl) into the LPBN induced an increase of 0.3 M NaCl intake (15.6 ± 5.7 and 21.5 ± 3.5 ml/210 min, respectively, vs. saline: 1.7 ± 0.8 ml/210 min) and an early inhibition of water intake (3.5 ± 1.4 and 6.7 ± 2.1 ml/150 min, respectively, vs. saline: 9.2 ± 1.4 ml/150 min). The pretreatment of the LPBN with 2-hydroxysaclofen (GABAB antagonist, 5 nmol/0.2 μl) potentiated the effect of baclofen on 0.3 M NaCl intake in the first 90 min of test and did not modify the inhibition of water intake induced by baclofen in cell-dehydrated rats. Baclofen injected into the LPBN did not affect blood pressure and heart rate.Conclusions: Thus, injection of baclofen into the LPBN in cell-dehydrated rats induced ingestion of 0.3 M NaCl and inhibition of water intake, suggesting that even in a hyperosmotic situation, the blockade of LPBN inhibitory mechanisms with baclofen is enough to drive rats to drink hypertonic NaCl, an effect independent of changes in blood pressure. © 2013 Kimura et al.; licensee BioMed Central Ltd.
Keywords: Baclofen; Dehydration; Lateral parabrachial nucleus; Sodium appetite; Thirst; baclofen; sodium chloride; water; animal cell; animal experiment; animal model; animal tissue; blood pressure; controlled study; dehydration; fluid intake; heart rate; hyperosmotic stress; male; nonhuman; parabrachial nucleus; plasma osmolarity; priority journal; rat; sodium intake; Animals; Arterial Pressure; Drinking; Functional Laterality; GABA Agonists; GABA Antagonists; Heart Rate; Male; Osmolar Concentration; Pons; Rats; Rats, Wistar; Saline Solution, Hypertonic